Optimization of extraction methods for determination of phosphodiesterase-5 (PDE5) inhibitors in premix coffee - Zailina, A.M; Aminah, A; Mohd Ambar, Y (Universiti Kebangsaan Malaysia, 2013)
An efficient analytical technique capable of analyzing three most common phosphodiesterase-5 (PDE5) inhibitors (vardenafil, sildenafil and tadalafil) simultaneously in premix coffee was developed. Sample extractions using either acetonitrile or methanol with two different extraction techniques (with and without evaporation steps) were evaluated. Identification and quantitation was conducted by high performance liquid chromatography with photo-diode-array (HPLC-DAD) at different wavelengths; 230 nm, 245 nm and 290 nm; and by time of flight mass spectrometry (LC-MS-TOF). Extraction with acetonitrile (without evaporation with nitrogen) showed recovery ranging from 105% to 113% (± <10%) for HPLC-DAD at 245 nm and 93% to 102% (± <2.5%) for LC-MS-TOF. Chromatogram separation was best achieved with mobile phase consisted of water (0.1% formic acid) and acetonitrile (0.1% formic acid) with gradient elution within 20 min. Thus, the results indicated that extraction using acetonitrile without evaporation step was the most efficient technique for determination of PDE5 inhibitors in premix coffee.